Results of Single incision Hallux Valgus Surgery - Sultan N. Qasim FRCS (Tr & Orth); Lee Elzubeir; Maneesh Bhatia MBBS, FRCS (Tr&Orth) (Foot & Ankle Orthopaedics, 2016)
Category: Bunion Introduction/Purpose: Soft tissue release is an integral part of Hallux Valgus surgery and is traditionally performed through an additional dorsal first web space incision. We performed a review of Hallux Valgus correction with Scarf +/- Akin osteotomy using single medial incision with lateral release performed through the same incision. Methods: The study included 202 feet operated by a single surgeon between July 2009 and July 2014. Average age of patients at the time of operation was 60 years +/- 14. Patient satisfaction survey was conducted at the time of study. Patients with minimum follow up of 12 months post surgery were included in this study. The average follow up at the time of study was 45+/- 18 months. Pre-operative and final post-operative radiographic data was collected for Hallux Valgus angle, Intermetatarsal angle, Distal Metatarsal Articular Angle and Medial Sesamoid Position. The average Mean radiological follow up duration was 6.7 months. Results: Mean Hallux Valgus Angle improved from 33.2 to 15.6 degrees, Intermetatarsal angle improved from 14.4 to 7.8 degrees, Distal Metatarsal Articular Angle improved from 17.6 to 9.8 and Medial Sesamoid Position improved from 3 to 1 [p < 0.05 for each variable]. Response rate was 78% (Very satisfied 69%, Satisfied 14%, Satisfied with reservation 11%, Dissatisfied 6%). There was no correlation of any preoperative or postoperative radiographic measure with satisfaction grade. Two patients had intraoperative fracture with no long term sequelae. No patient required revision procedure. Conclusion: Single medial incision surgery for Scarf +/- Akin Osteotomy for Hallux Valgus Correction is a simple, safe and effective technique with very high satisfaction. The results are comparable to, if not better that, traditional two-incision surgery thus questions requirement of a second dorsal first web space incision.